Suppression of gyrase-mediated resistance by C7 aryl fluoroquinolones. Issue 7 (16th March 2016) - Malik, Muhammad; Mustaev, Arkady; Schwanz, Heidi A.; Luan, Gan; Shah, Nirali; Oppegard, Lisa M.; de Souza, Ernane C.; Hiasa, Hiroshi; Zhao, Xilin; Kerns, Robert J.; Drlica, Karl
Abstract : Fluoroquinolones form drug-topoisomerase-DNA complexes that rapidly block transcription and replication. Crystallographic and biochemical studies show that quinolone binding involves a water/metal-ion bridge between the quinolone C3-C4 keto-acid and amino acids in helix-4 of the target proteins, GyrA (gyrase) and ParC (topoisomerase IV). A recent cross-linking study revealed a second drug-binding mode in which the other end of the quinolone, the C7 ring system, interacts with GyrA. We report that addition of a dinitrophenyl (DNP) moiety to the C7 end of ciprofloxacin (Cip-DNP) reduced protection due to resistance substitutions in Escherichia coli GyrA helix-4, consistent with the existence of a second drug-binding mode not evident in X-ray structures of drug-topoisomerase-DNA complexes. Several other C7 aryl fluoroquinolones behaved in a similar manner with particular GyrA mutants. Treatment of E. coli cultures with Cip-DNP selectively enriched an uncommon variant, GyrA-A119E, a change that may impede binding of the dinitrophenyl group at or near the GyrA-GyrA interface. Collectively the data support the existence of a secondary quinolone-binding mode in which the quinolone C7 ring system interacts with GyrA; the data also identify C7 aryl derivatives as a new way to obtain fluoroquinolones that overcome existing GyrA-mediated quinolone resistance.